Profil Hematologi Ikan Gabus (Channa striata Bloch, 1793) - Ari Hepi Yanti, Esti Lestari, Tri Rima Setyawati, (Jurnal Protobiont, 2017)
The hematology profile that include hematocrite value, erythrocyte count, leucocyte count, differential leucocyte can used to determined the health state and diagnosis of fish diseases. The purpose of this research is to study the hematology profiles of gabus (C. striata). This research was conducted on August to October 2016. Gabus with body length about 25-35 cm and the blood samples were collected from vena caudalis (caudal vein) to evaluate hematocrite value, erythrocyte count, leucocyte count, eythrocyte and leucocyte diameter and differential leucocyte. The result of the research showed that hematocrite values 23,25-24,83%, erythrocyte counts 2,34-2,51x106cell/mm3, erythrocyte diameter 7,69-8,16 Î¼m, leucocyte counts 1,53-1,65x105cell/mm3, leucocyte diameter 5,73-6,53 Î¼m, monocytes 5,73-6,53%, limphocytes 76,13-78,20% and neutrophils 16,07-17,40%.